Building a Living Memory for the History of Our Present: New Perspectives on Archival Appraisal - Wallot, Jean-Pierre (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
AbstractThis paper examines the practical and theoretical problems that confront archivists — and historians — today. Because of the information overload in our world and of the complexity, diversity, and fragility of supporting media, the way archivists are now choosing archival records, and the very nature of the records retained, are radically changing. The paper summarises the latest thinking that is revolutionising the way archivists do their work. It also clarifies the present strategy of the National Archives of Canada insofar as public records are concerned.